Leadership of Madrasa Heads In The Management of Institutions Based On Accreditation Instruments 2024 - Andiesgo, Johan; Falah, Retno Annisa Nurul; Muis, Muhammad Aufa (Al-Qalam Institue, 2025)
This study examines the leadership of madrasa heads in managing institutions, drawing on the 2024 accreditation instruments, and highlights the crucial role of leadership in ensuring quality education. Effective leadership by madrasa heads is a key factor in creating a high-quality institution. Using a qualitative approach and field research, this study collects data through interviews, document reviews, and observations to explore the leadership practices of madrasa heads. Data analysis follows a qualitative framework, incorporating data triangulation, which involves stages of data reduction, presentation, and verification. The findings reveal that the leadership of madrasa heads has been effective in managing educational institutions by the 2024 accreditation standards. Key factors influencing this leadership include work quality, work effectiveness, and communication. This research highlights the importance of strong leadership in achieving accreditation goals and improving madrasa management.